Aggrecan is degraded by matrix metalloproteinases in human arthritis. Evidence that matrix metalloproteinase and aggrecanase activities can be independent. - Fosang, A J (1996)
Proteolytic degradation of aggrecan is a hallmark of the pathology of arthritis, yet the identity of the enzyme(s) in cartilage responsible for this degradation is unknown. Previous studies have suggested that the matrix metalloproteinases (MMPs) may be involved but there has been no definitive evidence for their direct action in the proteolysis of aggrecan in human arthritis. We now show unequivocally that aggrecan fragments derived from the specific action of MMPs can be detected in synovial fluids from patients with both inflammatory and noninflammatory arthritis, with a neoepitope monoclonal antibody AF-28 that detects the NH2-terminal sequence F342FGVG.... The synovial fluid MMP fragments were of low buoyant density and distributed exclusively at the top of cesium chloride density gradients, suggesting that these fragments lacked chondroitin sulfate chains. AF-28 immunoblotting of synovial fluid aggrecan fragments revealed a population of small AF-28 fragments of 30-50 kD. Based on their size relative to characterized products of an MMP-8 digest (Fosang, A.J., K. Last, P. Gardiner, D.C. Jackson, and L. Brown. 1995, Biochem. J. 310:337-343), these AF-28 fragments were derived from proteinase cleavage at, or near, the ...ITEGE373 / ARGSV... aggrecanase site. Immunodetection with polyclonal anti-ITEGE antiserum revealed that these fragments lacked the ...ITEGE374 COOH terminus and were not therefore products of aggrecanase action. The same fluid samples contained a broad 68-90-kD G1 fragment that contained the COOH-terminal ...ITEGE374 neoepitope. The results suggest that in some circumstances, despite extensive proteolysis of the core protein, aggrecan molecules may be cleaved by MMPs or aggrecanase in the interglobular domain, but not both.